Diseño y construcción de un banco didáctico de alumbrado y cierre centralizado del vehículo - Palta Tello, Brayan Fabricio (2022)
The objective of this degree work is to design and build a didactic bench for the lighting system and centralized locking of the vehicle with the purpose of granting the necessary equipment to carry out practices and verifications to the students of the automotive engineering career of the National University of Loja, thus complementing the theoretical foundations with practical qualities. A review was made of the evolution over time of lighting and centralized locking systems, as well as the theoretical foundations on which these systems base their operation. Regarding the design of the didactic bench, it was carried out to consider anthropometric criteria focused on the latin american population to obtain the appropriate dimensions; the analyzes for the choice of material were carried out through the Expert Choice software using the hierarchical analysis method (AHP), getting as a result, the black structural tube, black cold-rolled steel plate and MDF wood for the construction of the bench. The centralized lighting and locking bank equip the same components which would be found in a conventional vehicle, assembled in a didactic way so that, through connection terminals listed according to regulations, the connection of the corresponding system can be made, in addition, seven practical guides and a use and maintenance manual to support the bank, its proper use and the prevention of associated risks. As a final part, an evaluation was made of the students of the automotive engineering career to know the level of satisfaction concerning the didactic bench, practical guides and user manual, where 80% rate the ergonomics of the lighting bench as excellent and the case of the central locking bench, 73% of those surveyed indicated its ergonomics as excellent. Keywords: Lighting system, central locking system, educational bench, lights, vehicle, electrical system.